Integrated Animal Waste Management - Sutton, Alan L.; Power, James F.; Day, Donald L.; Fontenot, Joseph P.; Forster, D. Lynn; Huber, Don M.; Jones, Don D.; Kelling, Keith A.; McCaskey, Thomas A.; Moore, James A.; Safley Jr., Lawson M. (Council for Agricultural Science and Technology (CAST), 1996)
A broad spectrum of integrated manure management systems are available to collect, transfer, store, treat, and efficiently utilize a great variety of sources and nutrient qualities of animal manures.
Keywords: Animal Waste Management; Integrated Animal Waste; Animal Manure